The effect of surgical timing on operative duration and quality of reduction in Type III supracondylar humeral fractures in children - Murnaghan, M. Lucas (Springer Berlin Heidelberg, 2010)
PURPOSE: To determine the influence of the time from injury to surgery of Type III supracondylar fractures on operative duration and quality of reduction. METHODS: A retrospective review of Type III supracondylar fractures treated by closed reduction and percutaneous pinning over a 3-year period was performed. RESULTS: The subjects were divided into two groups based on the time from injury to surgery (IST): Group 1 (<8 h) 48 subjects and Group 2 (>8 h) 39 subjects. There was no difference in the mean age or gender ratio between the two groups. There were no cases of compartment syndrome or conversion to open reduction in either group. The mean IST was 669 min. The mean IST for Group 1 was 340 min and it was 1,074 min for Group 2. The operative duration for Group 1 was 32.56 min and for Group 2 it was 31.72 min (P = 0.77). There were no significant differences in the quality of reduction. CONCLUSIONS: There was no difference in the operative duration demonstrated between IST <8 h and IST >8 h. This failure to demonstrate a difference should not be interpreted as demonstrating equivalence. This study does not conclude that all displaced supracondylar fractures should be delayed, though it does inform the surgeon that, if compelled to delay surgery, this series did not demonstrate an increased risk of complications, nor a worsened quality of reduction.